(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the role of the antidiabetic medication gliclazide on the galectin-3 expression, a biomarker associated with cardiac fibrosis and diastolic dysfunction, in those suffering from diastolic dysfunction of the left ventricle and type 2 diabetes. Study Design: Cross-section study Place and Duration of Study: This study was conducted at the Al-Diwaniyah Teaching Hospital in Diwaniyah, Iraq from 1st February 2023 to 31st December 2023. Methods: A total of 62 patients with type 2 diabetes mellitus and left ventricular diastolic dysfunction were enrolled. Two groups were divided; one for gliclazide therapy and the other for control. Gliclazide group was given standard treatment for type 2 diabetes mellitus plus gliclazide while the control group received standard treatment alone. Results: Galectin-3 expression was measured at baseline of treatment using quantitative real-time polymerase chain reaction (qRT-PCR) .The results showed that gliclazide treatment significantly increase in galectin-3 expression relative to the group under control. Galectin-3 levels have decreased levels correlated with improvements in left ventricular diastolic dysfunction parameters, including left ventricular filling pressure and diastolic function. Additionally, gliclazide treatment was associated with improved glycemic control, as evidenced by reduced HbA1c levels. Conclusion: Gliclazide may have no beneficial effect on left ventricular diastolic dysfunction in patients with type 2 diabetes mellitus by modulating galectin-3 expression. The upregulation of galectin-3 may contribute to the deterioration in diastolic function observed with gliclazide treatment. It is necessary to do additional research to clarify the underlying mechanisms and validate these findings in a larger patient group.